Narrativas de professores da Educação de Jovens e Adultos: retrato do CEJA Jacira Caboclo - Cavalcante Filho, João da Costa (2018)
This research is presented with the intention to understand the construction of the sociological portrait of an educational institution: the CEJA Jacira Caboclo, from the narratives of four teachers, in the context of practice teaching in adult education (EJA). Thus, the theoretical-methodological research carried out through an approach that collaborate with our research objectives that were anchored in the benchmark of sociological portraits (LAHIRE, 2004). For that, by the construction of personalised teaching portrait of the researcher who, in their narratives, shows up in the contexts of personal and professional life. In this way, the teachers ' narratives of adult and youth education have become benchmarks for the construction of the sociological portrait of CEJA Jacira Caboclo, in line with the personal and professional lives of these educators. In this perspective, the analysis of the routes if marked in two lines of investigation:) the first if has excelled by exploiting the person and Professional active in youth and adult education (EJA), analyzing, so, the contexts of family origins, the motivation for the choice of the teaching profession, the exercise of teaching as work and teaching in adult and youth education. (b)) the second, from the perspective that the narratives of the teachers of the EJA revealed the existence of professionals committed to challenging contexts of adult and youth education. In this way, teachers of adult and youth education must be valued because they wish to contribute to the success of students formed by young people and adults who, at some point in life had difficulties of all kinds to study at age, and return to school in order to complete your training on the requirements of the world of work. Therefore, the sociological portrait of CEJA Jacira Caboclo reveals a space of possibilities around the training of teachers from their personal and professional experiences on the picture of total absence of continuing training in service by the competent organs in the construction of a training itinerary.